The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2020gb006672
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential for Mobilization of Old Soil Carbon After Permafrost Thaw: A Synthesis of 14C Measurements From the Northern Permafrost Region

Abstract: The magnitude of future emissions of greenhouse gases from the northern permafrost region depends crucially on the mineralization of soil organic carbon (SOC) that has accumulated over millennia in these perennially frozen soils. Many recent studies have used radiocarbon (14 C) to quantify the release of this "old" SOC as CO 2 or CH 4 to the atmosphere or as dissolved and particulate organic carbon (DOC and POC) to surface waters. We compiled~1,900 14 C measurements from 51 sites in the northern permafrost reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 131 publications
6
32
1
Order By: Relevance
“…This could suggest that the increase of vegetation growth in permafrost free areas, which increases the input of labile DOC from plant exudates into aquatic environments, will strongly influence diffusive CO2 and CH4 emissions from thermokarst lakes of Nunavik in Northern Quebec. These results are similar to other studies highlighting that diffusive CH4 and CO2 fluxes from lakes incorporate large proportions of modern carbon (Cooper et al, 2017;Dean et al, 2020;Elder et al, 2019).…”
Section: Accepted Articlesupporting
confidence: 92%
See 3 more Smart Citations
“…This could suggest that the increase of vegetation growth in permafrost free areas, which increases the input of labile DOC from plant exudates into aquatic environments, will strongly influence diffusive CO2 and CH4 emissions from thermokarst lakes of Nunavik in Northern Quebec. These results are similar to other studies highlighting that diffusive CH4 and CO2 fluxes from lakes incorporate large proportions of modern carbon (Cooper et al, 2017;Dean et al, 2020;Elder et al, 2019).…”
Section: Accepted Articlesupporting
confidence: 92%
“…In contrast, the palsa lakes dissolved CH4 and DIC contained inputs of centennial aged permafrost carbon, and the palsa lakes ebullition CH4 and SAS river DIC contained inputs from even older carbon sources. The difference in CH4 and DIC between the peatland and non-peatland lakes is broadly consistent with previous studies (Elder et al, 2018;Dean et al, 2020) that have found that the geological substrate and soil type exerts a strong influence on the age of carbon emitted from lacustrine CH4 and CO2 fluxes.…”
Section: Accepted Articlesupporting
confidence: 91%
See 2 more Smart Citations
“…For example, Arctic and Boreal surface waters receive ~100 Tg of dissolved organic carbon (DOC) each year from terrestrial ecosystems, a third of which (~35 Tg C yr −1 ) they deliver to the Arctic Ocean and surrounding seas (Abbott, Jones, et al, 2016; Kicklighter et al, 2013; McGuire et al, 2009). Radiocarbon measurements suggest that more than 80% of this DOC is modern—fixed since the 1950s (Qu et al, 2017; Raymond et al, 2007; Wild et al, 2019)—and even under extreme warming scenarios, DOM from degrading permafrost will likely remain a small proportion of total DOM flux (Abbott et al, 2015; Abbott, Jones, et al, 2016; Estop‐Aragonés et al, 2020; Laudon et al, 2012). However, when biolabile DOC (BDOC) and nutrients from permafrost mix with modern DOM, they could influence mineralization rates and alter the net ecosystem carbon balance of the permafrost zone (Abbott et al, 2014; Larouche et al, 2015; Textor et al, 2019), potentially resulting in greater CO 2 efflux from permafrost ecosystems to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%